Theoretical analysis of a three-phase bidirectional isolated DC-DC converter using phase-shifted modulation - Tan Z.Y.; Tan N.M.L.; Hussain I.S. (Institute of Advanced Engineering and Science, 2023)
A three-phase bidirectional isolated dc-dc converter consists of two six-pulse two-level active converters that enable bidirectional power flow by introducing a lag phase-shift angle of one converter with respect to the other converter. This paper explains the operating modes of a three-phase bidirectional isolated dc-dc converter in detail, taking into account the transfer of energy between the dc voltage sources and high-frequency ac inductances in the three-phase bidirectional isolated dc-dc converter. The power flow of the dc-dc converter is also examined based on the operating modes. 2018 Institute of Advanced Engineering and Science. All rights reserved.